Cardiac workload and skeletal muscle oxygenation during incremental exercise in healthy subjects - Tommi Jeskanen; Rasmus I. P. Valtonen; Venla P. Ylinen; Jan Nissinen; Mikko P. Tulppo (Physiological Reports, 2025)
Abstract We hypothesized that skeletal muscle oxygenation, measured by Near‐infrared spectroscopy (mNIRS), is associated with cardiac workload during incremental exercise. Healthy subjects (n = 30, age 27 ± 6, 15 females) performed a maximal exercise test starting from 0 W, following an incremental protocol starting from 40 W and increasing load every 2 min until exhaustion. Systolic blood pressure and breath‐by‐breath gas exchanges were measured to analyze oxygen uptake and respiratory compensatory point (RCP). Tissue saturation index (TSI) by mNIRS was measured from vastus lateralis. The slopes of TSI and rate pressure product (RPP) were calculated using the values from 0 W to 100% of the RCP threshold. RPP was 31,734 ± 3909 mmHg·bpm, and TSI was 50.0% ± 8.4% at the intensity of RCP. RPP and TSI slopes were 3463 ± 541 and −2.75 ± 1.68, respectively. In linear regression analysis, RPP slope was used as a dependent variable, and sex, body fat %, maximal oxygen uptake, hemoglobin, baseline SBP, and TSI% slope were used as predictor variables; TSI slope was the only variable associated with RPP slope (r = 0.60, p = 0.001). Cardiac workload during submaximal exercise, documented by RPP slope calculated over equal metabolic exercise intensities for all subjects, is partly regulated by skeletal muscle oxygenation, potentially due to the differences in microcirculation and/or mitochondrial properties in healthy young subjects.